Digital Health Literacy and Surgical Information - Seeking Behaviour: A Cross Sectional Survey - Mayank Asmit; Bhartendu Kumar; Tauseef Kibria; Soofia Firdaus; Md Khalid Tanweer; Sadaf Kibria (Journal of Pharmacy and Bioallied Sciences)
Background: In an era marked by technological advancements and increased digital information accessibility, digital health literacy has emerged as a pivotal factor in healthcare decision-making. Methods: A cross-sectional survey involving 400 participants was conducted. Digital health literacy, information sources, frequency of surgical information seeking, and factors influencing information-seeking behavior were assessed. Data analysis included descriptive statistics and inferential tests. Results: The study found diverse digital health literacy levels, with 45% in the moderate category. Social media (60%) and healthcare websites (70%) were primary information sources. A significant portion (30%) frequently sought surgical information online. Trust in online information (mean = 3.85), perceived usefulness (mean = 4.12), and access barriers (mean = 2.95) played crucial roles. Digital health literacy influenced information seeking, with moderate literacy individuals (60%) being the most engaged. Conclusion: Understanding digital health literacy and information-seeking behavior is vital for patient empowerment and healthcare decision-making. Tailored interventions should target trust-building, perceived usefulness, and access barriers.